2019
DOI: 10.5507/fot.2018.015
|View full text |Cite
|
Sign up to set email alerts
|

Three new freshwater species of the genus Achnanthidium (Bacillariophyta, Achnanthidiaceae) from Taiping Lake, China

Abstract: We describe three new Achnanthidium species, A. lacustre sp. nov., A. sublanceolatum sp. nov., and A. taipingensis sp. nov., from Taiping Lake, Anhui Province (China) based on light and scanning electron microscopy. A. lacustre sp. nov. belongs to the "A. minutissimum complex" of the genus, based on it having straight external distal raphe fissures and round to elliptical areolae. Both A. sublanceolatum sp. nov., and A. taipingensis sp. nov. belong to the "A. pyrenaicum complex" of the genus, based on them hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…nov., and A. taipingensis P.Yu, Q.M.You et Kociolek sp. nov. from the benthos of Taiping Lake in the Anhui Province (Yu, You, Kociolek, & Wang, 2019), and A. mediolanceolatum P.Yu, Q.You et Kociolek sp. nov., A. parvulum Q.You, P.Yu et Kociolek sp.…”
Section: Taxonomy and Systematicsmentioning
confidence: 99%
“…nov., and A. taipingensis P.Yu, Q.M.You et Kociolek sp. nov. from the benthos of Taiping Lake in the Anhui Province (Yu, You, Kociolek, & Wang, 2019), and A. mediolanceolatum P.Yu, Q.You et Kociolek sp. nov., A. parvulum Q.You, P.Yu et Kociolek sp.…”
Section: Taxonomy and Systematicsmentioning
confidence: 99%
“…The diatom genus Achnanthidium Kützing (1844) was originally described by Kützing, as a subgenus of the Achnanthes Bory de Saint-Vincent (1822). The species Achnanthes microcephalum Kützing was the type species of the subgenus (Pérès et al 2014;Yu et al 2019a). In the 1990s, Round et al (1990) resurrected Achnanthidium and elevated it to the genus level.…”
Section: Introductionmentioning
confidence: 99%
“…Species belonging to Achnanthidium commonly, abundantly, and frequently occur in various freshwater habitats, such as streams, rivers, and lakes (Potapova & Ponader 2004, Kobayasi et al 2006, Pinseel et al 2015, Karthick et al 2017, Krahn et al 2018. Moreover, Achnanthidium species can occur across a broad range of freshwater habitats, from oligotrophic to eutrophic waters (Potapova & Hamilton 2007, Karthick et al 2017, Krahn et al 2018, Yu et al 2019. However, species recognition within the genus Achnanthidium has presented some challenges in terms of research.…”
Section: Introductionmentioning
confidence: 99%
“…To date, three complexes have been characterized in the Achnanthidium genus: (1) members of the A. minutissimum (Czarnecki 1994: 157) complex, have straight external distal raphe ends, and striae density that increase towards the apex; (2) members of the A. pyrenaicum (Kobayashi 1997: 148) complex, have external distal raphe ends that deflect or hook to one side of the valve; and (3) members of the A. exiguum (Czarnecki 1994: 157) complex, have external distal raphe ends curved in opposite directions (Round & Bukhtiyarova 1996, Krahn et al 2018, Pinseel et al 2015, Compère & Van de Vijver 2011, Jüttner et al 2011, Yu et al 2018, 2019. Currently, more than 200 Achnanthidium species have been reported in the literature worldwide (Marquardt et al 2017, Yu et al 2019. In China, roughly 60 Achnanthidium species have been reported (Liu et al 2013, Wang & Deng 2017, Yu et al 2017, but only a few have been reported as new species (Yu et al 2018, 2019, Liu et al 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation